ENTREPRENEURSHIP SUPPORT: A CONTENT ANALYSIS APPROACH - Shena Levina; Aluisius Hery Pratono; Suyanto Suyanto (Perpustakaan Universitas Surabaya, 2018)
Abstract - Entrepreneurship support for start-up and developing businesses are sought to free the ability of entrepreneurship to address a number of economic and social challenges. However, the significant scale of many such efforts raises a question regarding the ability of politicians and civil servants to intervene effectively in the support of entrepreneurs. This article aims to understand the entrepreneurship support regarding the key players and their role to enhance the ability of entrepreneurship. This research used two case studies to compare the similarities and differences among the cases. The first study observed the entrepreneurship supports in the food sector business and the music school business.